Knowledge and intelligent computing techniques in bioinformatics. (2016) - Anand, Divya; Pandey, Babita; Pandey, Devendra Kumar
Knowledge-based systems (KBS) and intelligent computing techniques (ICT) are widely used in the field of bioinformatics. A number of techniques have been applied for the interpretation and analysis of biological data. KBS consists of case based reasoning (CBR) whereas ICT consists of artificial neural network (ANN), fuzzy logic (FL), data mining techniques (DMT), swarm intelligence (SI) and evolutionary algorithm (EA). The aim of this review is to introduce briefly the various KBS and ICT and their integration such as ANN-DMT, CBR-DMT, EA-ANN, EA-DMT, EA-ANN-DMT, ANN-SI, ANN-FL, ANN-SI-EA-FL, EA-FL, EA-SI etc. which are applied in the field of bioinformatics. This study is exhibited in the form of a table which includes application area, intelligent technique used, machine learning task and the database/databank used. This study will help the novice researchers to choose appropriate KBS and ICT to deal with the challenges encountered during representation, integration, analysis, interpretation and management of biological data.